Titanium Allergy: Is Zirconia a Viable Alternative? - Ana Sofi a de Sousa Moreira; Ana Patrícia Silva MAgalhães; Bruno Miguel Santos Carvalho; Juliana Cardoso Costa Santos; Ana Isabel Pereira Portela; Mário Ramalho de Vasconcelos (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Purpose: Highlight and discuss the properties of zirconia compared to titanium, in the case of titanium allergies. Materials and methods: The research was divided into 3 themes: Titanium Allergies: clinical cases reported, with the key-words: Titanium allergy; Dental Implants, in the databases MEDLINE / PubMed, Google Scholar and the archives of the library of the Faculty of Dental Medicine, University of Porto. Results: Dental implants are a good approach for replacement of lost teeth. Titanium and titanium alloys are the material of choice for fabrication of dental implants. However there is a possibility of allergic reactions occur. In that way, zirconia seems to be a potential alternative to titanium implants because of its biocompatibility, mechanical properties, aesthetics and low plaque affi nity. Conclusions: Zirconia dental implants have the potential to become an alternative however further clinical scientifi c information is needed.